PENGARUH PERPUTARAN MODAL KERJA TERHADAP PROFITABILITAS PADA PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI LQ45 PERIODE 2014-2021 - Mismah Adila; Shinta Avriyanti (JAPB, 2022)
Working capital functions to finance all processes of operational activities and all forms of corporate procurement. Working capital in every company must be in a state of rotation, this is what is commonly referred to as working capital turnover. Working capital turnover can show the relationship between sales and working capital. Working capital is one of the factors that can affect profitability. The aims of the research are 1) to find out whether there is an effect of working capital turnover on profitability, 2) to find out how much influence working capital turnover has on profitability in property and real estate companies in LQ45 for the 2014-2021 period. This type of research approach is descriptive quantitative. The sampling technique uses documentation techniques. With a population of all property and real estate sector companies listed on the Indonesia Stock Exchange (IDX) until 2021, namely 35 companies. The number of samples is four companies from 2014 to 2021. The location of this study is the website of the Indonesia Stock Exchange (IDX) using simple linear regression analysis as data analysis using SPSS software version 25. The results of this study indicate that there is an effect of turnover working capital on profitability in property and real estate companies listed on LQ45 for the 2014-2021 period and the magnitude of the effect of working capital turnover on profitability in property and real estate companies on LQ45 for the 2014-2021 period is 52.1%, while the other 47.9% influenced by other variables not examined in this study. Keywords: Working Capital Turnover, Profitability, LQ45, SPSS.